Males of Neotropical social wasps (Vespidae, Polistinae, Epiponini) recognize colonies with virgin females - Pizarro, Laura Chavarria; Noll, Fernando Barbosa [UNESP] (Pensoft Publ, 2014)
Male behavior of Neotropical swarm-founding wasps has rarely been observed. The few published observations about male activities only describe their behavior during the short period they spend inside nests. In consequence, virtually nothing is known about what they do outside the colonies, and even less is known about mating behavior. This paper provides the first report of Epiponini males arriving at a colony with virgin females. The behavior of males and workers after queen removal was observed in one colony of Chartergellus communis located at a farm in Pedregulho, Sao Paulo, Brazil. The day after queen elimination, males were observed outside the nest. When males tried to enter the nest, workers aggressively attacked them. These attacks were similar to the defensive behavior used when foreign conspecifics attempt to enter the nest. The aggressive workers response and the absence of males before queen removal indicated that the males did not belong to the colony. Additionally, no fights were observed between individuals before queen removal. It is likely that foreign males arrived at the colony to mate with virgin females. Observations suggest that epiponine males are able to find nests with virgin females in mature stages of the colony cycle, and that mating can occur during different stages of the colony cycle.
Keywords: Males; Social wasp; queenless; colonies